POLÍTICAS PÚBLICAS Y COMBATE A LA POBREZA EN SAN LUIS POTOSÍ. - Trejo, Lucero Espinosa; Mballa, Louis Valentin (European Scientific Journal, ESJ, 2015)
In this paper, the concept of poverty is taken up from the different approaches of the organizations in the world. We emphasize the situation of poverty in the state of San Luis Potosi in Mexico. This research allows the public to know that the government implements strategies to reduce poverty in San Luis Potosi, focusing on a program "National Crusade against Hunger" and its diffusion and impact on the beneficiaries thereof. It discusses the different events, from the implementation of this program, presenting the most important achievements and results to determine their effectiveness. This basic research is documentary; it is based on journal publications and review of literature and especially the officials of the "National Crusade against Hunger".